2005
DOI: 10.1111/j.1600-0463.2005.apm_245.x
|View full text |Cite
|
Sign up to set email alerts
|

High prostate cancer mortality in Norway: Influence of Cancer Registry information?

Abstract: Norway has among the highest prostate cancer mortality rates in the world. The aim of the present project was to assess whether this can be explained by the unique routine procedure of information transfer from the Cancer Registry of Norway (CR) to the Norwegian Cause of Death Registry (COD Registry). Norwegian prostate cancer patients deceased during 1996 were identified (n=2012). The information basis of the official mortality statistics was reviewed by two physicians, who independently identified the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
0
18
1
2
Order By: Relevance
“…Evaluation of the quality of prostate cancer data reported to the Cancer Registry has shown a completeness of nearly 100%, 14 and the close collaboration between the registries has resulted in highly reliable information on prostate cancer as underlying cause of death. 15 Our information on recreational physical activity was based on questionnaires that allows for subjective interpretation of the questions and individual perception of the activity, and thus, misclassification of physical activity can be influenced by many factors, such as age, social context and seasonal variations. 16 However, validation studies have shown that questionnaires may be able to classify people into broad categories of physical activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the quality of prostate cancer data reported to the Cancer Registry has shown a completeness of nearly 100%, 14 and the close collaboration between the registries has resulted in highly reliable information on prostate cancer as underlying cause of death. 15 Our information on recreational physical activity was based on questionnaires that allows for subjective interpretation of the questions and individual perception of the activity, and thus, misclassification of physical activity can be influenced by many factors, such as age, social context and seasonal variations. 16 However, validation studies have shown that questionnaires may be able to classify people into broad categories of physical activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The unique 11-digit identity number of Norwegian citizens was used to link individuals from the HUNT Study to information on cancer incidence at the Cancer Registry of Norway (15,16) where stomach cancer was registered according to the International Classification of Diseases, Seventh Edition codes 151.0, 151.8, and 151.9. Reporting to the Cancer Registry is mandatory, and since 1953, all new cancers diagnosed in Norway have been registered with information on affected organ, subsite within the organ, and histologic type (17).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, information was collected on a range of lifestyle and health-related factors, including measures of physical activity, smoking, alcohol consumption, marital status and education. In addition, participants completed a self-administered questionnaire at home (for return in a pre-stamped envelope) that included the validated International Prostate Symptom Score (IPSS), 17 which was used to rate LUTS severity as no (0), mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) LUTS. The population in Nord-Trønde-lag County (127,000 residents) is stable, with a net out-migration of 0.3% per year (1996)(1997)(1998)(1999)(2000), and is ethnically homogenous (less than 3% non-Caucasian).…”
Section: Study Populationmentioning
confidence: 99%